Principles and medical applications of gene editing by CRISPR / Cas - Rolando Sánchez Artigas; María Teresa Díaz Armas; Raisa Rodríguez Duque; Pedro Enrique Miguel Soca (Medisur)
CRISPR/Cas technology is a simple, fast and extremely efficient method for gene editing. In order to describe the principles and medical application of this technology, a bibliographic review was carried out in Pubmed, SciELO, academic Google and the Cochrane Library, with the descriptors “gene editing”, “genome editing”, “CRISPR-Cas systems”, and “CRISPR-associated protein 9”. The CRISPR/Cas9 system comprises a Cas endonuclease and two types of RNA. Cas cuts the invading phage DNA into segments, which are integrated into the CRISPR sequence as spacers. Subsequently, the CRISPR sequence is transcribed to generate crRNA and tracrRNA, which form a double-stranded RNA structure that recruits Cas for cleavage. The introduction of the system into the cell interior occurs with plasmids, RNA or ribonucleoproteins. A nuclear localization sequence allows CRISPR / Cas9 to enter the nucleus. CRISPR/Cas9 technology is an efficient tool for precise gene editing with great impact on scientific research.